Anthocyanins in purple colored fruits. - Khoo, Hock Eng; Chew, Lye Yee; Ismail, Amin; Azlan, Azrina (Nova Science Publishers, 2012)
The occurrence of purple color in many fruits is due to the presence of a group of natural pigments called anthocyanins. On top of the economic importance of anthocyanins in industries as natural colorants, these pigments have important implications in human nutrition. Purple-colored fruits such as blackberry, grape, plum, and prune have high content of anthocyanins. Canarium odontophyllum fruit (locally known as dabai) is one of the popular indigenous fruits of Borneo Island that turns into purple when ripen. Dabai represents an almost similar complex system to that of many other purple-colored fruits since anthocyanins are formed in the skin. Besides that, phenolic compounds from phenolic acid to various subclasses of flavonoids have been identified in the fruit. Total anthocyanins content in dabai fruit was comparable to that of blackberry and grape. It is also noted that the total flavanols of dabai fruit was much higher than those purple fruits. In purple-colored berries, anthocyanins as the major pigment are present together with appreciable amount of flavanols. In addition, flavonols particularly quercetin and kaempferol are found as co-pigment for fruits coloration in the berries. Numerous reviews on the potential roles of anthocyanins in reduction of disease risk factors and prevention of cardiovascular health problems have been documented. The compounds revealed consistent effects through different aspects of vascular health (platelet aggregation, atherosclerosis, blood pressure, antioxidant status, and inflammation-related markers), myocardial conditions, and whole-body metabolism (serum biochemistry and lipid profile). Purple-colored fruits are good sources of anthocyanidins that offer vast arrays of health-promoting properties.